User-generated visibility: Secondary gatekeeping in a shared media space. (February 2014) - Singer, Jane B
This article explores implications of the transition to an environment in which users have become secondary gatekeepers of the content published on media websites. This expanded user role, facilitated by technology and enabled by digital news editors, includes assessment of contributions by other users; communication of the perceived value or quality of user- and journalist-produced content; and selective re-dissemination of that content. The result is a two-step gatekeeping process, in which initial editorial decisions to make an item part of the news product are followed by user decisions to upgrade or downgrade the visibility of that item for a secondary audience. Preliminary empirical evidence indicates these user gatekeeping capabilities are now pervasive on US newspaper sites.